Travel and tourism - Sharpley, Richard (Sage Publications, 2015)
Offers an introduction to the subject of travel and tourism that helps readers extend their understanding of key concepts and enhance their thinking skills in line with course requirements. This book provides support on how to revise for exams, how to present calculations and how to prepare for and write assessed pieces.